Ecoregion and community structure influences on the foliar elemental niche of balsam fir (Abies balsamea (L.) Mill.) and white birch (Betula papyrifera Marshall). Issue 9 (11th September 2022) - Heckford, Travis R.; Leroux, Shawn J.; Vander Wal, Eric; Rizzuto, Matteo; Balluffi‐Fry, Juliana; Richmond, Isabella C.; Wiersma, Yolanda F.
Abstract: Changes in foliar elemental niche properties, defined by axes of carbon (C), nitrogen (N), and phosphorus (P) concentrations, reflect how species allocate resources under different environmental conditions. For instance, elemental niches may differ in response to large‐scale latitudinal temperature and precipitation regimes that occur between ecoregions and small‐scale differences in nutrient dynamics based on species co‐occurrences at a community level. At a species level, we compared foliar elemental niche hypervolumes for balsam fir ( Abies balsamea (L.) Mill.) and white birch ( Betula papyrifera Marshall) between a northern and southern ecoregion. At a community level, we grouped our focal species using plot data into conspecific (i.e., only one focal species is present) and heterospecific groups (i.e., both focal species are present) and compared their foliar elemental concentrations under these community conditions across, within, and between these ecoregions. Between ecoregions at the species and community level, we expected niche hypervolumes to be different and driven by regional biophysical effects on foliar N and P concentrations. At the community level, we expected niche hypervolume displacement and expansion patterns for fir and birch, respectively—patterns that reflect their resource strategy. At the species level, foliar elemental niche hypervolumes between ecoregions differed significantly for fir ( F = 14.591, p ‐value = .001) and birch ( F = 75.998, p ‐value = .001) with higher foliar N and P in the northern ecoregion. At the community level, across ecoregions, the foliar elemental niche hypervolume of birch differed significantly between heterospecific and conspecific groups ( F = 4.075, p ‐value = .021) but not for fir. However, both species displayed niche expansion patterns, indicated by niche hypervolume increases of 35.49% for fir and 68.92% for birch. Within the northern ecoregion, heterospecific conditions elicited niche expansion responses, indicated by niche hypervolume increases for fir of 29.04% and birch of 66.48%. In the southern ecoregion, we observed a contraction response for birch (niche hypervolume decreased by 3.66%) and no changes for fir niche hypervolume. Conspecific niche hypervolume comparisons between ecoregions yielded significant differences for fir and birch ( F = 7.581, p ‐value = .005 and F = 8.038, p ‐value = .001) as did heterospecific comparisons ( F = 6.943, p ‐value = .004, and F = 68.702, p ‐value = .001, respectively). Our results suggest species may exhibit biogeographical specific elemental niches—driven by biophysical differences such as those used to describe ecoregion characteristics. We also demonstrate how a species resource strategy may inform niche shift patterns in response to different community settings. Our study highlights how biogeographical differences may influence foliar elemental traits and how this may link to concepts of ecosystem and landscape functionality. Abstract : Foliar elemental niches, defined by axes of carbon (C), nitrogen (N), and phosphorus (P), reveal the ecophysiological responses of species to environmental conditions at regional and local scales. Our study shows that species exhibit biogeographical specific elemental niches likely driven by biophysical ecoregion differences as well as how changes in niche structure occur in response to different community types across scales. Our study highlights biogeographical differences relating to foliar elemental traits linking concepts of ecosystem and landscape ecology.